Iranian EFL Learners’ Perceptions towards Demotivation in Learning English - Paziresh, Abbas; Hessamodini, Nilofar; Jafari, Zohre (Journal of Modern Languages, 2022)
Demotivation in learning English has always been challenging for teachers, parents and researchers and they sought ways to discover its roots and solve it. One important source of solutions to learners’ demotivation is their own perceptions. However, such a rich resource of information on demotivation has received little attention. Therefore, inspired by such a gap, the present study investigated Iranian high school EFL students’ perceptions of demotivation in learning English. Following quantitative survey research, a questionnaire was designed both inspired by demotivation questionnaires of Sakai and Kikuchi (2009) and Falout and Maruyama (2004) and teachers’ focus group on attitudes. It was created based on the Likert Scale and composed of three phases including 54 statements about teachers, textbooks and classroom conditions. The questionnaire was sent to 300 volunteer high school students selected from a random list of public and private high schools across the country. After completion, the questionnaire data were controlled and entered into SPSS. Then, descriptive statistics were computed and Pearson correlation and Runs Test were carried out. However, analysis of the learners’ perceptions revealed that students attributed their demotivation to teachers, classroom conditions, and textbooks respectively. It was found that in Iran, teachers were deemed not qualified enough to motivate students. Apart from that, the classroom conditions and English textbooks were in poor conditions and did not manage to attract and motivate learners.